Explaining Czech Inflation by a Time-Varying Taylor Rule - Pokorný, Tomáš (2021)
In this thesis, we empirically and theoretically analyze the time-variability of the Czech National Bank’s Taylor rule policy parameters. Firstly, we estimate the time-varying policy parameters via Kalman filter in the state-space model for the period of 1995Q1-2020Q3. Secondly, we use the estimated parameters in a theoretical non-linear New Keynesian dynamic stochastic general equilibrium (DSGE) model of a small open economy to test the implications of time-variability of the policy parameters for the economy. The thesis contributes to understanding the dynamics of inflation resulting from an inconsistency of monetary policy parameters. We find that the weight on the inflation gap has gradually decreased in the last two decades. From the impulse-response analysis, we find that unanticipated shocks to the policy parameters harm the inflation stability and increase the business cycles fluctuations.